Adjuvant Corticosteroids With Surgery for Chronic Subdural Hematoma: A Systematic Review and Meta-Analysis - Shi, Min; Xiao, Ling-fei; Zhang, Ting-bao; Tang, Qing-wen; Zhao, Wen-yuan (Frontiers in Neuroscience, 2021)
The use of adjuvant corticosteroids with surgery for chronic subdural hematoma (CSDH) has received considerable attention in recent years. However, there is no conclusive evidence regarding its effectiveness and safety for chronic subdural hematoma. Therefore, we performed a meta-analysis and systematic review to evaluate the effectiveness and safety of corticosteroids as an adjuvant treatment for the treatment of CSDH. We comprehensively searched electronic databases (PubMed, EMBASE, Cochrane Library, and Web of Science) to identify relevant trials that investigated the efficacy and safety of adjuvant corticosteroids with surgery for CSDH, published from inception until May 2021. Outcome measures included recurrence rate, all-cause mortality, good functional outcome, length of hospitalization, and adverse events. We used the Cochrane risk of bias method to evaluate the quality of randomized controlled trials (RCTs), and the Newcastle Ottawa Scale to evaluate the quality of observational studies. We included nine studies, consisting of three randomized controlled trials and six observational studies, that compared corticosteroids as an adjuvant treatment to surgery with surgery alone. Pooled results revealed that the risk of recurrence was significantly reduced in patients who received adjuvant corticosteroids with surgery compared to those who underwent surgery alone (relative risk [RR] = 0.52, 95% confidence interval [CI] = 0.39–0.69, p < 0.00001). However, no statistically significant difference was observed between these groups in all-cause mortality (RR = 0.91, 95% CI = 0.37–2.23, p = 0.83), good functional outcome (RR = 1.03, 95% CI = 0.96–1.10, p = 0.47), length of hospitalization (MD = 0.35, 95% CI = −2.23 to 1.67, p = 0.83), and infection rates (RR = 0.99, 95% CI = 0.64–1.53, p = 0.95). Adjuvant corticosteroids with surgery reduce the risk of recurrence of CDSH, but do not improve the all-cause mortality or functional outcome, as compared to surgery alone. These findings support the use of adjuvant corticosteroids with surgery for CSDH patients. Further high-quality RCTs are required to confirm the efficacy and safety of adjuvant corticosteroids in the treatment of CSDH patients.